Sociocultural dimensions of health: contributions to studies on risk, digital sociology, and disinformation (RECIIS, 2023)
Deborah Lupton is a renowned academic whose research has made significant contributions to the field of digital sociology and the sociocultural dimensions of medicine and public health. In an interview with Reciis, Lupton discusses one of the main contemporary challenges - misinformation and fake news - through the lens of digital sociology and addresses the sociocultural perspectives of risk based on the release of the third edition of her book Risk. In this edition, she includes a new chapter on the issues related to risk and the spread of misinformation during the COVID-19 pandemic. With comments on the Australian and Brazilian scenarios, Lupton delves into the issues of anti-science, denialism, and the role played by populist governments in combating the disease. Finally, she explores the potential of creative methods in qualitative studies, especially those that seek to understand people's rationalities, logics, and feelings.